Oral Proteasomal Inhibitors Ixazomib, Oprozomib, and Delanzomib Upregulate the Function of Organic Anion Transporter 3 (OAT3): Implications in OAT3-Mediated Drug-Drug Interactions - Yunzhou Fan; Zhengxuan Liang; Jinghui Zhang; Guofeng You (MDPI AG, 2021)
Organic anion transporter 3 (OAT3) is mainly expressed at the basolateral membrane of kidney proximal tubules, and is involved in the renal elimination of various kinds of important drugs, potentially affecting drug efficacy or toxicity. Our laboratory previously reported that ubiquitin modification of OAT3 triggers the endocytosis of OAT3 from the plasma membrane to intracellular endosomes, followed by degradation. Oral anticancer drugs ixazomib, oprozomib, and delanzomib, as proteasomal inhibitors, target the ubiquitin-proteasome system in clinics. Therefore, this study investigated the effects of ixazomib, oprozomib, and delanzomib on the expression and transport activity of OAT3 and elucidated the underlying mechanisms. We showed that all three drugs significantly increased the accumulation of ubiquitinated OAT3, which was consistent with decreased intracellular 20S proteasomal activity; stimulated OAT3-mediated transport of estrone sulfate and p-aminohippuric acid; and increased OAT3 surface expression. The enhanced transport activity and OAT3 expression following drug treatment resulted from an increase in maximum transport velocity of OAT3 without altering the substrate binding affinity, and from a decreased OAT3 degradation. Together, our study discovered a novel role of anticancer agents ixazomib, oprozomib, and delanzomib in upregulating OAT3 function, unveiled the proteasome as a promising target for OAT3 regulation, and provided implication of OAT3-mediated drug-drug interactions, which should be warned against during combination therapies with proteasome inhibitor drugs.